(untitled) (KASBIT Business Journal, 2021)
Traditional ecological knowledge (TEK) has been established as a valid contributor to environmental preservation in indigenous societies. Scholars have expanded upon this significance to benefit urban and rural ecologies, with most work being done in rural and geographically remote contexts around the world. In the urban context, academics have employed TEK predominantly to societal landscapes, including city planning, architecture, and ethnobiology. Scant attention has been paid to TEK manifestation in urban individuals’ lifestyles. Our research catalogues urban household TEK practices, by studying modern-day individuals in metropolitan Karachi - Pakistan, through a qualitative study design through thematic analysis. Data was collected through 21 indepth interviews of affluent and highly educated professionals, to document behaviours of a conventionally non-traditional respondent segment. Findings demonstrated a clear presence of TEK-based behaviours in modern urban individuals. These behaviours manifested in two types of perceived advantages: environmentally beneficial, and personally beneficial. This study is among the first to explore the adoption of TEK by urban individuals for environmental conservation and answers the call for making TEK more inclusive to address current environmental challenges. Keywords: Traditional ecological knowledge, pro-environmental behaviours, environmental conservation, urban households, indigenous wisdom.